Microwave Pyrolysis of Woody Biomass: Influence of Radiation Power on the Composition of Conversion Products; Applied Sciences; Vol. 13, iss. 13 - Shvets A. S. Anatoly Sergeevich; Vershinina K. Yu. Kseniya Yurievna; Vinogrodsky K. Kirill; Kuznetsov G. V. Geny Vladimirovich (2023, 2023)
Title screen